Evaluasi Arachis pintoi sebagai Biomulsa dalam Memperbaiki Kesuburan Tanah pada Pertanaman Jagung di Kemiringan Lahan yang Berbeda - Ade Sumiahadi; Muhamad Ahmad Chozin; Dwi Guntoro (Institut Pertanian Bogor, 2023)
Expanding agricultural land by using sloping dry land can be detrimental to the environment due to soil erosion and degradation. However, cover crops can be one of the technologies applied to reduce these risks. Arachis pintoi is one of cover crops that can be used as bio mulch on agricultural land. The study aimed to evaluate the effect of A. pintoi bio mulch on soil nutrient contents and maize plant growth at different slopes. A nested randomized block design was used in the study. Two levels of land used as the main factor and the type of mulch consisting of five levels (without mulch with weeding, without mulch without weeding, silver-black plastic mulch, straw mulch, and A. pintoi bio mulch) were used as the second factor. The results showed that A. pintoi bio mulch significantly increased the P content of the soil and could potentially increase several other macronutrients, especially C-organic, N, and Ca. The use of A. pintoi bio mulch with a cover technique that was left to cover the entire soil surface suppressed the growth and yield of maize plants compared to the control treatment. Keywords: cover crops, mulch, ornamental peanut, soil fertility, rice straw